„Valaki megmondaná, hogyan kell felkészülni a legrosszabbra?” A Covid-járvány okozta testi-lelki állapotok pasztorálpszichológiai reflexiója - Lilla SZABÓNÉ-LÁSZLÓ (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
„Could Anyone Explain How to Prepare Man for the Worst?” – Pastoral-Psychological Reflection on Physical and Mental Conditions Caused by the COVID-19. This study provides a theological reflection on suffering by identifying various conditions caused by the COVID-19 and post-COVID syndrome. A distinction is to be made between fear and symptoms on the one hand and anxiety and suffering on the other. Fear and symptoms potentially cause anxiety, and suffering thus creates existentially defined states wherein our faith and spirituality are highly significant. Different approaches are adopted in this paper: the problem-focused and emotion-focused approach, as explained by Lazarus and Folkman, and the religious coping methods and styles of Kenneth I. Pargament. The collaborative coping style (researched by Pargament) is not just the most effective approach, but it is one of the potential ways of inner spiritual growing. In order to find answers regarding suffering and anxiety, we have to meet Jesus and follow him on his descending path (repentance, humility, obedience – via purgativa), make reconciliation (via iluminativa), and receive the new creation (via unitiva). Congregations can search these ways together so that faith communities might gain strength and find possibilities in pastoral and spiritual care during the time of COVID-19.